Spinoza's Ethics : an introduction - Nadler, Steven M., 1958- (Cambridge introductions to key philosophical texts., 2006)
Nadler explains the doctrines and arguments of the Ethics and examines the philosophical background to Spinoza's thought and the dialogues in which Spinoza was engaged. He shows why Spinoza's endlessly fascinating ideas may have been so troubling to his contemporaries, as well as why they are still highly relevant today.